Influence of financial development on energy intensity subject to technological innovation: Evidence from panel threshold regression - Uddin, Md. Kamal; Pan, Xiongfeng; Saima, Umme; Zhang, Chengming (Energy (Oxford), 2022)
Controlling energy intensity has become a prime objective of present time as energy consumption is the main source of about three-fourth of the world's green house gas emissions. Therefore, scholars have been trying to detect the ways that can ensure efficient utilization of energy with minimal degradation of environment. Consequently, studies have been conducted to explore the linkages between financial development and energy consumption to see whether financial development can help reduce energy intensity. Nonetheless, this study considers technological innovation as a crucial dimension of socio-economic changes and explores the technology dependency of the influence of financial development on energy intensity. To do so, a panel threshold regression model is applied in a panel of 23 European Union (EU) countries. The results corroborate that the inhibiting effects of banking sector development, stock market development and overall financial development on energy intensity depend on the levels of technological innovation. Thus, policymakers need to consider the matter carefully when they devise policy decisions. •Threshold impact of financial development (FD) on energy intensity (EI) is studied.•Panel threshold regression model is applied for empirical analysis.•The impact of FD on EI is found as subject to technological innovation.•Stock market FD and overall FD impact energy intensity in same way.•Banking sector FD impacts energy intensity in different way.